Climate change litigation: issues and challenges (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The contribution analyzes the main trends of climate change litigation, against both public entities and private parties, in Italy and abroad, highlighting the most relevant procedural issues. Starting from the famous "Giudizio universale", the first Italian climate litigation case brought before the civil court in Rome (with elements of originality compared to previous European litigation experiences), the contribution will address the legal foundation of the actions (or causa petendi), the locus standi, even in collective forms, the most appropriate fora (court or arbitration) and their reciprocal relationship, the effectiveness of protection, the causation link and the the applicable law.
Keywords: Climate litigation; giudizio universale; effectiveness of protection; locus standi; causation link